Corneal Backscatters as an Objective Index for Assessing Fuchs' Endothelial Corneal Dystrophy: A Pilot Study. (2nd July 2017) - Chu, Hsueh-Yen; Hsiao, Ching-Hsi; Chen, Phil Yeong-Fong; Ma, David Hui-Kang; Chang, Chee-Jen; Tan, Hsin-Yuan
Abstract : Purpose . To provide an objective, quantitative approach for monitoring Fuchs' endothelial corneal dystrophy (FECD), with Scheimpflug imaging. Design . This is a retrospective case-control pilot study. Methods . The study group consisted of 53 eyes in 27 patients diagnosed with FECD, with normal subjects paired as control. Main outcome measures were corneal thickness, morphological patterns on densitograms, and indices of corneal density including the average area density (mean AD) and the average ratio of Descemet's membrane density versus area density (DM/AD) in Pentacam Scheimpflug images. Results . There were no significant differences in age and corneal thickness between FECD and normal groups. Morphologically, hanging-hammock patterns were noted on the densitograms of FECD patients, which were different from the high-back chair patterns in normal subjects. Quantitatively, mean AD and DM/AD were both elevated in FECD patients as compared with normal subjects (P = 0.01 and 0.025, resp.). In addition, FECD patients with corneal edema had significantly higher mean AD (P = 0.018 ) than those without corneal edema. Conclusions . This pilot study shows that Pentacam system provides an objective, quantitative way to approach FECD corneas. It can assist ophthalmologists in detecting the early change and in monitoring disease progression of FECD. Further studies are needed to consolidate the findings.